STATES OF STRENGTH AND DEFORMATION OF REINFORCED CONCRETE ELEMENTS IN BENDING - Ahmadaliyev Abdulxafiz Hasanboy ogli; Abdurakhmanov Ulugbek Arabdjon ogli (Journals Park Publishing, 2022)
This article describes the work done to determine the deformations of composite reinforced flexible beams in concrete and reinforcement, measuring the slope of the beam, the location and width of cracks formed in the beam.
Keywords: stress, deformation, deformation state, strength and deformation indicators